Pengaruh Penggunaan Media Zooming Presentation dalam Model Pembelajaran Inkuiri Terbimbing terhadap Hasil Belajar Siswa Kelas X SMA Negeri 2 Parepare (Studi Pada Materi Pokok Ikatan Kimia) - Umriana U; Sulfikar Sulfikar; Muh. Yunus (ChemEdu, 2021)
The research is a quasi-experimental that aimed to know the effect of discovery learning model by scientific approach toward student’s achievement in class X MS SMA Negeri 12 Bulukumba. The independent variable in this experiment was discovery learning model by scientific approach and the dependent variable was student’s achievement on electrolyte and non electrolyte solution subject matter. The population was class X MS SMA Negeri 12 Bulukumba that consisted of 140 students. Taking technique of sample was random sampling. The sample of this research consisted of two classes, namely class X MS2 as an experiment class with 26 students and class X MS3 as a control class with 25 students. The data of this research were gathered by testing the student’s achievement on electrolyte and non electrolyte solution subject matter. Data analysis technique was done by descriptive and inferential analysis. The hypothesis test by t-test was gathered tcalculated =2.68 more bigger than t(0.05;49)=2.00. Conclude that discovery learning model by scientific approach gives effected toward student’s achievement of class X MS SMA Negeri 12 Bulukumba on electrolyte and non electrolyte solution as subject matter.